2022
DOI: 10.7196/sajog.2022.v28i2.2097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and sociodemographic factors associated with antenatal depression among women in Limpopo Province, South Africa

Abstract: Background. Pregnancy-related depression is a common psychiatric disorder and a major public health concern in both developed and developing countries, but the disorder receives little attention and few resources, particularly in developing countries.Objectives. To assess the prevalence of antenatal depression and its sociodemographic risk factors among pregnant women in Limpopo Province, South Africa.Methods. This was a cross-sectional descriptive study conducted in a district hospital from 8 March to 12 Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…In contrast, our results did not find a significant association between a low educational level and depression and anxiety during pregnancy, but previous research has consistently shown a link between lower educational levels and antenatal depression [ 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, our results did not find a significant association between a low educational level and depression and anxiety during pregnancy, but previous research has consistently shown a link between lower educational levels and antenatal depression [ 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Semi-structured questionnaires adapted from WHO ASSIST V3 were used to measure behavioral aspects such as alcohol, tobacco, khat chewing, and other substance use ( 31 ). Pregnant women who used substances such as tobacco, khat, and alcohol only for non-medical purposes during this pregnancy were deemed to be currently using substances, while participants who used substances like these before the current pregnancy were considered to have ever used substances ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…In developed countries, a meta-analysis study found that the prevalence rates of depression were 7.4% (2.2–12.6%), 12.8% (10.7–14.8%), and 12.0% (7.4–16.7%) during the first, second, and third trimesters, respectively ( 10 ). A high prevalence of depressive symptoms or probable depression during pregnancy has been reported from developing countries, i.e., 18% in Bangladesh ( 29 ), 24.8% in Nepal ( 30 ), 25 % in Pakistan ( 22 ), 20.2 % in Brazil ( 19 ), 39 % in South Africa Cape Town ( 20 ), 38.5 % in South Africa KwaZulu-Natal ( 21 ), 31% in Limpopo Province South Africa ( 31 ), 39.5 % in Tanzania ( 28 ), 26.9% in Ghana ( 32 ), 29.4% in Nigeria ( 33 ), and 15.2 %−35.4% in Ethiopia ( 9 , 34 36 ).…”
Section: Introductionmentioning
confidence: 99%